The Yatela gold deposit: 2 billion years in the making. (December 2015) - Hein, K.A.A.; Matsheka, I.R.; Bruguier, O.; Masurel, Q.; Bosch, D.; Caby, R.; Monié, P.
Abstract: Gold mineralisation in the Yatela Main gold mine is hosted in a saprolitic residuum situated above Birimian supracrustal rocks, and at depth. The supracrustal rocks comprise metamorphosed calcitic and dolomitic marbles that were intruded by diorite (2106 ± 10 Ma, 207 Pb/ 206 Pb), and sandstone-siltstone-shale sequences (youngest detrital zircon population dated at 2139 ± 6 Ma). In-situ gold-sulphide mineralisation is associated with hydrothermal activity synchronous to emplacement of the diorite and forms a sub-economic resource; however, the overlying saprolitic residuum hosts economic gold mineralisation in friable lateritized palaeosols and aeolian sands (loess). Samples of saprolitic residuum were studied to investigate the morphology and composition of gold grains as a proxy for distance from source (and possible exploration vector) because the deposit hosts both angular and detrital gold suggesting both proximal and distal sources. U–Pb geochronology of detrital zircons also indicated a proximal and distal source, with the age spectra giving Archaean (2.83–3.28 Ga), and Palaeoproterozoic (1.95–2.20 Ga) to Neoproterozoic (1.1–1.8 Ga) zircons in the Yatela depocentre. The 1.1–1.8 Ga age spectrum restricts the maximum age for the first deposition of the sedimentary units in the Neoproterozoic, or during early deposition in the Taoudeni Basin. Models for formation of the residuum include distal and proximal sources for detritus into the depocentre, however, it is more likely that material was sourced locally and included recycled material. The creation of a deep laterite weathering profile and supergene enrichment of the residuum probably took place during the mid-Cretaceous-early Tertiary. Highlights: We present research on the geology of the Yatela gold mine in Mali. We investigate the morphology and composition of gold grains. We present new geochronological data on the age of host rocks and the deposit. We present a new model for the formation of auriferous residuum in the deposit.